Properties of alkali-activated concrete (AAC) incorporating demolished building waste (DBW) as aggregates. Issue 1 (1st January 2021) - Pyngrope, Mebanteiskhem; Hossiney, Nabil; Chen, Yu; Thejas, H K; Sarath, Chandra K; Alex, Jacob; Lakshmish Kumar, Srinidhi
Abstract: This study was undertaken to evaluate the potential of demolished building waste (DBW) as aggregates in alkali-activated concrete (AAC). A recent road-widening activity led to the demolition of commercial buildings along National Highway 275, Bangalore-Bantwal, India. DBW was collected from these sites and processed manually at the laboratory facility of CHRIST (Deemed to be University). Processing of DBW was done to obtain both waste coarse and fine aggregates from demolished concrete and brick waste units, respectively. AAC was synthesized by fly ash, ground granulated blast furnace slag, sodium hydroxide, sodium silicate, along with waste aggregate replacement rates of 0, 25, 50, and 75% by weight of natural aggregates. Fresh and hardened properties of developed concrete mixtures were experimentally determined. Results of the study indicate that 28-day compressive strength of 30.4 and 21 MPa was obtained for AAC with 25 and 50% DBW aggregates, which was 8.6 and 36.9% lower than control mix, respectively. Further, there was an increase in the water absorption and a reduction to acid resistance for all the AAC mixes with DBW aggregates. Based on the results obtained, it was observed that AAC with 25 and 50% DBW aggregates find great potential in civil engineering applications.